Estudio de factibilidad para crear una empresa denominada CROSSXTREME, Centro de Acondicionamiento Físico en el municipio de Cartago, Valle. (2015)
Crossxtreme is a functional service provider model, integrating utilities and benefits for a community such as the city of Carthage, is through a prepared innovative technique applied by the CAF that the aim to create a comprehensive service based on actual numbers thrown by the DANE are 131.63 people who currently inhabit the city of Carthage and to which , a population of 57.232, is should be subtracted to the 35% that make up the strata 1 and 2 as our target market 37.201. The price at the beginning of the serious business of • $40,000 based on study of acquisition for the population, through a direct channel. To start the process of provision of service it starts with legalization that regulations are required by the Constitution of society shares simplified model inspired by the law 1258. Considerations on the use of natural resources, an estimate of the types and amounts of landfilled waste and an evaluation of the direct effect of the project on the population, fauna, soil, air and water among others must be within the environmental impact study. This single project should focus on the treatment that will be residential, and similar waste will adopt a correct policy for the management of recycling and comply with. The investment that the project requires $52.094.494 distributed as follows, fixed by an investment of $44.049.908 and a working capital of $8.040.586.